Prevalence of Streptococcus dysgalactiae and Microbial Codetection in Patients Presenting with Pharyngitis. (4th October 2017) - Dawson, Paul; Malone, Leslie; Grigorenko, Elena
Abstract: Background: Streptococcus pyogenes (GAS) is often the only pathogen tested for when a patient presents with symptoms of pharyngitis. Widespread use of rapid strep tests create a diagnostic gap when pharyngitis is caused by other bacterial pathogens, such as Streptococcus dysgalactiae (GCGS). S. dysgalactiae often goes undetected in clinical samples, resulting in incorrect diagnosis as viral infection, and potentially leading to downstream negative sequela. In this study, we investigate the incidence of GCGS in patients symptomatic for pharyngitis and its co-detection with other viral and bacterial pathogens responsible for pharyngitis. Methods: Throat swabs ( n = 1799) from symptomatic patients were collected from February–March 2017. DNA from the specimens was extracted and tested on Target-Enriched Multiplex-PCR (TEM-PCR) respiratory panels. These panels test for the presence of common microbial pathogens responsible for pharyngitis with high sensitivity and specificity. Detection was performed on a microarray platform with complementary target-specific detection probes. Results: S. dysgalactiae was detected in 19 samples out of 1799 tested. The prevalence rates by age groups was 0.85% in patients younger than 15 years ( n = 1524) and 2.18% in patients older than 15 years ( n = 275). Of the 19 GCGS detections, 6 viral co-detections were observed: 4 with Influenza A and 2 with Rhinovirus. No co-detection with other bacterial pathogens including GAS ( n = 201), Chlamydophila pneumoniae ( n = 3) and Mycoplasma pneumoniae ( n = 12) were observed. Detection of Fusobacterium necrophorum ( n = 12) and Arcanobacterium haemolyticum ( n = 2) was also observed. GCGS and F. necrophorum were co-detected in 1 sample which had no viral presence. Conclusion: In this study, we show that GCGS prevalence in patients symptomatic for pharyngitis is second only to GAS and, in many cases, is not accompanied by viral co-detection. Since the pathogen often produces mild disease that mimics viral infection symptoms a misdiagnosis of the infection as viral and therefore non-treatable can result. The data presented here underscores the need to include the detection of an emerging cause of pharyngitis, S. dysgalactiae, despite suspected viral etiology, for more accurate therapeutic decisions. Disclosures: P. Dawson, Diatherix Laboratories, LLC: Employee,  Salary; L. Malone, diatherix: Employee,  Salary; E. Grigorenko, Diatherix Laboratories: Employee, Salary